Churchill's fractured neck of femur. (August 2019) - McLoughlin, Liam
In June 1962 at the age of 87 years, Sir Winston Churchill (1874–1965) fell over in his hotel room at the Hotel de Paris in Monte Carlo and sustained a fracture to the neck of his left femur. He was flown back to London and the fracture operated on at The Middlesex Hospital by two eminent orthopaedic surgeons, Mr Phillip Newman (1911–1994), Consultant to the The Middlesex Hospital and The Royal National Orthopaedic Hospital, Stanmore, and The Institute of Orthopaedics, London, and Professor Herbert Seddon (1903–1977), Consultant to the The Royal National Orthopaedic Hospital, Stanmore, and Director of The Institute of Orthopaedics under whom Churchill was admitted as a private patient. Churchill's recovery was complicated by the development of deep vein thrombosis. During his convalescence, Churchill befriended Seddon who recorded his time with him in his private papers. On 21 August, Churchill was discharged to his home at 28 Hyde Park Gate which had been modified during his admission and made a return to public life in November 1962 at a dinner at the dining club he had originally founded, The Other Club.